Applied Entrepreneurship Education at University of Manadonorth Sulawesi Indonesia - H. E. Sendouw, Recky; B. Kairupan, Sisca; A. Mege, Revolson (International Journal of Engineering and Technology, 2018)
The University of Manadoâ€™s (Unima) students have great potential to become successful entrepreneurs if they have good knowledge and adequate entrepreneurial skills. However, although entrepreneurship subject has been taught for years in several faculties, however it was hard to identify the studentsâ€™ entrepreneurs at Unima. By making use of qualitative method, this study examines student entrepreneurship development; and identify the factors that influence the development of student entrepreneurship at University of Manado. The conclusion is the entrepreneurship course at Unima before 2015 just focused on the theory, that is the reason why there was not start-up student entrepreneur. However, since the curriculum has been improving and more focus on applied entrepreneurship education, some students have successfully started their business. The factors that encourage entrepreneurship development at University of Manado are the support of various parties, both internal and external campus.Â